Effect of monosodium glutamate additive on the performance of dialysis membrane - Idris, Ani; Chan, Mieow Kee; Ahmed, Iqbal (University Putra Malaysia, 2007)

(untitled)
A novel dialysis membrane with monosodium glutamate (MSG) as an additive has been fabricated and its performance evaluated in terms of urea clearance. Nine formulations of casting solutions had been designed with 20% cellulose acetate, and different ratio of formic acid/MSG. The result shows that MSG based membrane with the 6 wt% of MSG, achieved the best urea clearance, 53.20%. SEM images illustrated that the increment of MSG in casting solution tend to promote macrovoids formation and finally transit to finger like structure. However, when the amount of MSG is further increased beyond 6 wt%, the urea clearance reduced and the macrovoids structure disappeared. Thus, enlarged finger like structure favors the dialysis process.